Compliance determination of domestic base of hygienic standards for carcinogenic substances in the atmospheric air of populated areas with EU requirements (Environment & Health, 2024)
The purpose of this work was to assess the safety of domestic (hygienic) standards for carcinogenic substances in the atmospheric air of populated areas and determine the concentration level corresponding to the acceptable risk indicator.Materials and methods. Bibliosemantic, bibliographic and hygienic research methods were used in this research. The results were obtained based on the collection and analysis of data on chemical carcinogenic compounds dangerous to humans, based on materials from international Directives, domestic regulatory frameworks and the IARC database.To assess the danger of individual substances and hygienic regulatory levels, risk indicators were determined according to recommended methodological documents. Indicators of reference concentrations for carcinogenic substances standardized in Ukraine were taken from data of the integrated risk information system (IRIS) US EPA.Results and discussion: the studies conducted indicate the need to revise the hygienic standards for carcinogenic substances included in the domestic regulatory framework for the atmospheric air of populated areas. The current standards for the most part exceed the level of acceptable or acceptable risk of probable cancer development among the population and those employed in production. This issue can be resolved by using an accelerated methodology, which is based on the calculation of the dose-risk scale. Accepted hygienic standards for the indicator of carcinogenic risk should be considered as annual averages for the atmospheric air of populated areas, and the current average daily concentrations according to international recommendations should be aimed at preventing acute exposure to chemical carcinogens within 24 hours and manifest themselves over a period of about 14 days.Conclusion: sanitary (hygienic) standards for carcinogenic substances in the air, included in the domestic bases, overwhelmingly exceed the level of permissible (acceptable) risk of cancer development and do not ensure safety for the population and persons involved in production and require revision in accordance with the requirements of the EU countries and the USA.It is proposed to resolve this issue using an accelerated methodology, which is based on the calculation of the dose-risk relationship (scale).
Keywords: carcinogenic substances; hygienic standards; atmospheric air; risk; dose-risk dependence; health hazard